Taxonomy and ecology of Neotropical Cassidinae (Coleoptera: Chrysomelidae) - Sekerka, Lukáš (Jihočeská univerzita, 2017)
This thesis investigates the systematics and biology of Neotropical Cassidinae and summarizes available knowledge of all tribes occurring in the Neotropics. This study uses a multidisciplinary framework to evaluate various issues in the taxonomy of this diverse group of beetles as a result of extensive field research.
Taxonomy and ecology of Neotropical Cassidinae (Coleoptera: Chrysomelidae)
Keywords: Coleoptera; Chrysomelidae; Cassidinae; taxonomy; nomenclature; classification; natural history